Tropical mycology: volume 2, micromycetes - Watling, R.; Ainsworth, A. M.; Ainsworth, A. M.; Frankland, J. C.; Frankland, J. C.; Isaac, S.; Isaac, S.; Robinson, C. H.; Robinson, C. H.; Watling, R. (Wallingford :CABI Publishing, 2002)
This second volume of Tropical Mycology contains 11 sections discussing the biology, taxonomy, phylogeny, physiology, anatomy and biochemistry of lichens and microfungi, including some plant pathogenic fungi.
Keywords: FF620 - Plant Pests, (New March 2000); ZZ333 - Microbial Ecology, (New March 2000); ZZ380 - Taxonomy and Evolution; ZZ392 - Morphology of Microorganisms, (New March 2000); ZZ394 - Biochemistry and Physiology of Microorganisms, (New March 2000)